Kajian Pendapatan Usahatani Bawang Daun (Allium Fistolosum,L.) di Desa Kuan Noel Kecamatan Fatumnasi Kabupaten Timor Tengah Selatan. - Estevao Mario Fernandes; Charles Kapioru; Paulus Un (Undana Press, 2019)
The research on the study of farming leaf onion (Allium Fistolosum I) income was carried this research was carried out in the village of Kuan Noel, sub-district of Fatumnasi, South Central Timor (TTS). The purpose of the study are: (1) to find out the Break Even Point, (2) to find out the income of the onion farming in the village of Kuan Noel and (3) to find out the relative benefits of farming onion. The determination of the location of the study was conducted by purposive sampling, with the consideration that Kuan Noel Village had a fairly high production of onion farming compared to other villages. Samples taken in the study or research were 46 people consisting 2 farmer groups. The analysis tool used in this study is the Break Event Point, income analysis tool and R/C Ratio. The resultsof the study or research show that (1) The level of production break event point is 454 Kg and the break event point prices is Rp 3.601, (2) total income of leaf onion farming is Rp. 1.008.584.964, and the average income received by farmers is Rp. 21.925.760, (3) R/C ratio of the leaf onion farming is 4,2. Penelitian tentang kajian pendapatan usahatani bawang daun (Allium fistolosum L) telah dilaksanakan di Desa Kuan Noel Kecamatan Fatumnasi Kabupaten Timor Tengah. Tujuan penelitian (1) untuk mengetahui Break Event Poin, (2) untuk mengetahui pendapatan usahatani bawang daun, (3) untuk mengetahui keuntungan relatif pada usahatani bawang daun. Penentuan lokasi penelitian dilakukan secara purposive sampling dengan pertimbangan Desa Kuan Noel memiliki produksi bawang daun yang tinggi. Sampel yang diambil dalam penelitian sebanyak 46 orang yang terdiri dari 2 kelompok tani. Hasil penelitian menunjukkan bahwa: (1) Tingkat break event point produksi sebanyak 454 Kg dan break event point harga sebesar Rp 3.601, (2) total pendapatan usahatani bawang daun sebesar Rp 1.008.584.964, rata-rata pendapatan yang diterima petani sebesar Rp 21.925.760, (3) nilai R/C Ratio usahatani bawang daun adalah 4,2.